From assessment to action: A randomised controlled trial of the effectiveness of a holistic diagnostic to enhance work ability - Fauser, David; Dötsch, Saskia; Roder, Jessica; Kleineke, Vera; Feddersen, Dagmar; Usdrowski, Gregor; Bethge, Matthias (Die Rehabilitation, 2025)
Employees can benefit from multimodal work-related intervention strategies. This randomised controlled trial tested the effectiveness of an integrative diagnostic service used to clarify intervention needs of employees with endangered work participation (German Clinical Trials Register: DRKS00027577).Employees with health restrictions and limited work ability were included and received an initial consultation with their occupational health physician. With computer-generated allocation lists, they were randomised to the treatment arms. The intervention group (IG) immediately attended a two-day assessment in a rehabilitation centre and then received follow-up consultations at the workplace. The control group (CG) started the two-day assessment six months after randomisation. Questionnaire data were collected from participants at their initial consultation and after six months. The primary outcome was the subjective work ability of the participants (Work Ability Score; 0–10 points). Secondary outcome measures included working conditions and sick leave duration.Data from 61 participants (IG: n=32) were analysed. A clinically important but statistically nonsignificant difference was found between IG and CG, including a moderate effect size for work ability (difference=1.15: 95% CI: −0.05 to 2.35; p=0.061). Clinically relevant differences were observed for sick leave duration in weeks (difference=−4.00: 95% CI: −7.49 to −0.51; p=0.025) and job insecurity (difference: −16.40; 95% CI: −29.82 to −2.99; p=0.017).Our results suggest that the intervention led to a reduction in sick leave and improvements in job security and work ability. The effectiveness of the intervention depends largely upon whether the needs of individuals and the requirements of workplaces are taken into consideration. Participants could be selected by occupational physicians on the basis of the occupational skill level. Further research should consider the long-term effects and health economic analyses and structural requirements for a nationwide implementation, as well as employers’ perspectives.
Keywords: work ability; occupational health; work participation; assessment; Rehabilitation